Design of experiments confirms optimization of lithium administration parameters for enhanced fracture healing. (3rd January 2018) - Vachhani, Kathak; Pagotto, Andrea; Wang, Yufa; Whyne, Cari; Nam, Diane
Abstract: Fracture healing is a lengthy process which fails in 5–10% of cases. Lithium, a low-cost therapeutic used in psychiatric medicine, up-regulates the canonical Wingless pathway crucial for osteoblastic mineralization in fracture healing. A design-of-experiments (DOE) methodology was used to optimize lithium administration parameters (dose, onset time and treatment duration) to enhance healing in a rat femoral fracture model. In the previously completed first stage (screening), onset time was found to significantly impact healing, with later (day 7 vs. day 3 post-fracture) treatment yielding improved maximum yield torque. The greatest strength was found in healing femurs treated at day 7 post fracture, with a low lithium dose (20 mg/kg) for 2 weeks duration. This paper describes the findings of the second (optimization) and third (verification) stages of the DOE investigation. Closed traumatic diaphyseal femur fractures were induced in 3-month old rats. Healing was evaluated on day 28 post fracture by CT-based morphometry and torsional loading. In optimization, later onset times of day 10 and 14 did not perform as well as day 7 onset. As such, efficacy of the best regimen (20 mg/kg dose given at day 7 onset for 2 weeks duration) was reassessed in a distinct cohort of animals to complete the DOE verification. A significant 44% higher maximum yield torque (primary outcome) was seen with optimized lithium treatment vs. controls, which paralleled the 46% improvement seen in the screening stage. Successful completion of this robustly designed preclinical DOE study delineates the optimal lithium regimen for enhancing preclinical long-bone fracture healing.